PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA OHSAS 18001:2007 PADA PELAKSANAAN PROYEK PEMBANGUNAN FLY OVER PASAR KEMBANG SURABAYA - Lokajaya, I Nyoman (Heuristic, 2015)
The purpose of this study was (1) Know the process of applying for K3 management system development projects Fly Over Flower Market Surabaya, (2) Getting the elements associated with OHSAS 18001:2007. From the analysis it was found that (1) monitoring and evaluation process of the construction SMK3 Fly Over Flower Market, is only intended to measure the level of implementation of SMK3 in fulfilling the terms of the security, safety and health at the site of construction activities carried out to the service user (PIU ), KDP, and the service provider. By adjusting the results of the monitoring and evaluation SMK3 into the element K3 OHSAS 18001:2007 Management, implementation SMK3 more profitable. The advantage is that its elements can be used to specify the K3 policy, planning, program objectives and K3. (2) Through Gap Analysis calculations using the Radar Chart, obtained K3 Management OHSAS 18001:2007 elements associated with the results of the monitoring and evaluation is an element SMK3 K3 Policy (clause 4.2) with a value of 94.00%, Planning (clause 4.3) with values 96.30%, Implementation and Operation (clause 4.4) with a value of 96.30%, Inspection and Repair (clause 4.5) with a value of 93.34% and Management Review (clause 4.6) with a value of 93.33%. It shows very well and in accordance with the implementation of the management system K3 is done through monitoring and evaluation.Kata kunci : fly over, gap analysis, OHSAS